(untitled) (Scientific journal of the Fergana State University, 2024)
The development of lexical competence is a crucial aspect of young learners’ language acquisition process. This abstract provides an overview of the methodology employed to enhance young learners’ lexical competence through the integration of comics in primary English classes. The use of comics as a pedagogical tool offers a visually engaging and textually rich medium that captivates students’ attention and facilitates vocabulary acquisition. This methodology involves designing purposeful activities, promoting language interaction and communication, and employing appropriate assessment methods. By incorporating comics into the classroom, teachers can create a dynamic and interactive learning environment that fosters students’ vocabulary acquisition and overall language development. This abstract highlights the significance of using comics as an effective methodology to enhance young learners’ lexical competence in primary English classes.